Penggunaan Media Digital Sebagai Promosi Dan Pemberdayaan POKDARWIS Menuju Desa Wisata Sukajadi Kab. Bogor Jawa Barat - Irwandy, Deddy; Kurnia Hidayati, Ratih; Raif Khadijah, Siti Adelita; Enjelita, Imel; Litzy Sruy, Raisel (PARAHITA : Jurnal Pengabdian kepada Masyarakat, 2024)
The climbing of Mount Salak in Sukajadi Village is one of the targets in supporting Bogor Regency Regional Regulation Number 7 of 2020 concerning the Bogor Regency Tourism Development Master Plan for 2020-2025. The problem in managing digital promotional materials has not been maximized and uses conventional methods. This community service is carried out with the aim of community partnership-based empowerment through efforts to use digital media as a promotion and empowerment of the Tourism Awareness Group (Pokdarwis) towards the Sukajadi Tourism Village, Bogor Regency, West Java. By increasing the ability and empowerment of Pokdarwis through digital content, basic tour guide skills and skills in creating promotional narratives, it can attract tourists and introduce local tourism potential, especially climbing Mount Salak through the Kalimati route. The methods used include training and mentoring Pokdarwis members on social media use, digital content creation, and knowledge of tour guides in tourist villages. The evaluation of the activity was conducted by measuring the participants' involvement in the training process, as well as their capacity to use digital media independently. The results show an increase in the understanding and skills of Pokdarwis members in utilizing digital media for tourism promotion, which is indicated by an increase in the number of followers and interactions on social media. The conclusion is that empowering Pokdarwis through the use of digital media can significantly support the development of Sukajadi Tourism Village as a more recognizable and attractive tourist destination for local and foreign tourists Keywords: Empowerment; Digital Media; Tourism; Pokdarwis; Tourism Village